Problematika Pembelajaran PAI di Era Digital - Aziz, Ahmad Husni; Fahrurrazi, Fahrurrazi; Akimmusolah, Akimmusolah; Rahmah, Alfiana Nur; Jaenullah, Jaenullah (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Education is a determinant of where a person will live his life. With education, it is hoped that a person will be able to become a human being who can create renewal and improvements. In education, it is inseparable from the problems found in both student factors, teachers, infrastructure and the environment around the Islamic Religious Education learning institution. The purpose of this study is to describe how Islamic religious education learning is in general, what problems are faced in Islamic Religious Education learning and what factors cause problems in Islamic Religious Education lessons and what steps are appropriate to overcome these problems. in Islamic religious education learning in the era of the industrial revolution 4.0. This era has directly or indirectly brought many changes in various lines of Islamic religious education life. Especially in relation to Islamic religious education learning in the classroom, one example is the emergence of online learning in the world of education. This era gave birth to the phenomenon of disruption which requires the world of Islamic religious education to also adapt. Islamic religious education is now faced with new challenges, problems, demands, and needs that have never existed before. Therefore, it is necessary to carry out updates and innovations to the system, governance, curriculum, human resource competency, facilities and infrastructure, culture, work ethic, and others.